Safety accessibility and sustainability: The importance of micro-scale outcomes to an equitable design of transport systems. (July 2017) - Tyler, N.
Abstract: This paper discusses the potential conflicts that can arise when trying to design a transport system to be sustainable, safe and accessible. The paper considers first the overarching vision that drives such an aim and how that determines choices for design and implementation of such schemes. Using the example of a shared space project, Exhibition Road in London, to illustrate how these issues come to arise and how research could help to resolve them, the paper then considers how science is able to support better design and implementation. This raises questions for scientific methods that could support better consideration of such issues, learning from the small-samples analysis of transport safety research to be amplified to include the detailed research that drives accessible design. Highlights: It is necessary to ensure that safe and sustainable transport system design is accessible Attention must be paid to macro-level (vision for a city) and micro-scale (design details of the transport system) The relationship between required and provided capabilities determines the accessibility details of the design Ensuring that design outcomes are equitable is the measure of how safe and accessible systems will be sustainable Research needs to develop robust methods for analysing the benefits of design detail in transport systems